A spiky pattern in the course of electrical thoracic impedance as a very early sign of a developing pneumothorax. (12th September 2016) - Cambiaghi, B.; Moerer, O.; Kunze‐Szikszay, N.; Mauri, T.; Just, A.; Dittmar, J.; Hahn, G.
Summary: A pneumothorax (PTX) is a potentially lethal condition in high‐risk intensive care patients. Electrical impedance tomography (EIT) has been proven to detect PTX at the bedside. A so far not described pattern in the course of thoracic impedance at an early state of PTX was observed in a pig model of ventilator‐induced lung injury (VILI) used for a more extensive study. EIT was performed at a framerate of 50 Hz. Beginning of PTX at normal ventilation, manifestation of PTX at VILI ventilation (plateau pressure 42 cm H2 O) and final pleural drainage were documented. At ventilation with 8·6 ml kg −1, early PTX findings prior to any clinical deterioration consisted in a spike‐like pattern in the time course of impedance (relative impedance change referred to initial end‐expiratory level). Spike amplitudes (mean ± SD) were the following: 0·154 ± 0·059 (right lung) and 0·048 ± 0·050 (left lung). At this state, end‐expiratory levels (mean ± SD) were still similar, −0·035 ± 0·010 (right) and −0·058 ± 0·022 (left). After application of VILI ventilation (38 ml kg −1 ), a PTX developed slowly, being confirmed by a continuous increase in the end‐expiratory level on the right side and diverging levels of +0·320 ± 0·057 (right) and −0·193 ± 0·147 (left) at full manifestation. We assume that spikes reflect a temporary change in the electrical pathway caused by leakage into the pleural cavity. This newly described phenomenon of spikes is considered to be a potentially useful indicator for a very early detection of an evolving PTX in high‐risk ICU patients.